Experience with a modified technique of free Gracilis transfer - Gautam, Biswas; Puneet, Tuli; Kavita, Kalitha (Indian Journal of Plastic Surgery, 2006)
Various techniques of harvesting the free Gracilis flaphave been described. The authors describe their experiencein the use of a ′limited′ incision in harvesting this flap, as compared to the long medial incision,for both a segmental as well as total flap harvest. Whole orpartial Gracilis harvest could be done using small incisions avoiding long scars using the conventional approach. Twenty-one free Gracilis muscle transfers were performed. In12, a short proximal curved incision was used to dissect asegment of the muscle with its pedicle and with an added small incision near the knee, the whole muscle could be dissected and delivered. The described technique of tracing the vascular pedicle by retracting both the borders of the adductor longus, was followed. This gave a better and easier access to the whole length of the pedicle, vis-à-vis the classic approach of dissecting the pedicle below the adductor longus, which was performed in nine cases.
Keywords: Gracilis flap; small incision; modified harvest